Empirical investigation on sectoral inequality, gender empowerment, education, and income inequality in Indonesia: Dynamic panel approach - Espa, Vitriyan; Suratman, Eddy; Wahyudi, (Asian Development Policy Review, 2025)
Sectoral inequality exemplifies the baseline condition; despite the same significant sectoral growth, high sectoral inequality also leads to high income inequality. This is because sectors with low contributions and sectors with high contributions to regional income will provide very unequal income for the workforce involved in them. Each variable may have a different relationship in the long term. This study aimed to investigate the short-term and long-term effects of Sectoral Inequality, Gender Empowerment Index (GEI), and Average Years of Schooling (AYS) on Income Inequality in Indonesia. The Vector Error Correction Model (VECM), based on panel data for the period 2015–2022, serves as the data analysis method. Each variable requires a different time to influence variations in other variables. The results show that there are no significant effects, either in the short run or in the long run, between Sectoral and Income Inequality. In the long-term, GEI does not affect Income Inequality but has an effect in the short-term. Meanwhile, AYS has a significantly negative effect on Income Inequality in the long-term and short-term. The practical implication of these research findings is that efforts from the government are needed to reduce Sectoral Inequality before encouraging equal distribution of sectoral growth to avoid high income inequality.